1958
DOI: 10.1037/h0043427
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Edwards' and McClelland's measures of achievement motivation.

Abstract: Independent measures of achievement motivation have recently been developed by Edwards (1) and McClelland et al. (2). Edwards' measure of this variable is one of fifteen that have their origin in, and bear the same names as, a list of manifest needs presented by Murray (3). They form the Edwards Personal Preference Schedule which measures a "number of relatively independent normal personality variables" (1, p. 1). Mc-Clelland's method of measuring n Achievement is also rooted in Murray, since he uses imaginati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1960
1960
1980
1980

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…T w o assumptions which underlie the interpretation of the results of this study are: ( a ) ICL data are more closely related to behavior; and ( b ) EPPS data are more closely related to needs. W e have offered the results of an unpublished study i n support of the ICL-behavior relationship, but other investigators (7,8 ) have found evidence which raises doubts as to the EPPS-needs (at least, needs in the T A T fantasy sense) relationship. One explanation, then, of our findings is that the EPPS and the ICL, which in the final analysis are both self-rating inventories, may be tapping very nearly the same level of behavior.…”
Section: Discussionmentioning
confidence: 92%
“…T w o assumptions which underlie the interpretation of the results of this study are: ( a ) ICL data are more closely related to behavior; and ( b ) EPPS data are more closely related to needs. W e have offered the results of an unpublished study i n support of the ICL-behavior relationship, but other investigators (7,8 ) have found evidence which raises doubts as to the EPPS-needs (at least, needs in the T A T fantasy sense) relationship. One explanation, then, of our findings is that the EPPS and the ICL, which in the final analysis are both self-rating inventories, may be tapping very nearly the same level of behavior.…”
Section: Discussionmentioning
confidence: 92%
“…This study adds to the already existing body of literature which debates the usefulness of these predictors. With respect to need for achievement, studies have shown that there does not seem to be an accurate, reliable way of measuring the construct (Molikan, 1958;AtkinsonandLitwin, 1960;Mitchell, 1961). Perhapsinthefuture, measurement could be facilitated by the development of an instrument which would quantify need for achievement in terms of a specific state, in this case, those motivations and goals directly associated with the academic setting.…”
Section: Discussionmentioning
confidence: 99%
“…1959; Robinson, 1964;Meyer, 1965 ;Heckhausen, 1967). However, the results are far from unequivocal and some studies have failed to find a relationship between ' n-Ach ' and academic performance (Walter, 1957;Haber, 1957;Molikan, 1958;Atkinson and Litwin, 1960 ;Mitchell, 1961). Some of the difficulties in obtaining reliable results and in predicting more than 50 per cent of the variance in academic achievement may be a function of the lack of control for (1) individual instructor effects, (2) the interaction between instructor and teaching method, (3) a lack of a consistent measure of the amount of information learned by students, and (4) a failure to consider the degree of correspondence between student preference for particular course conditions and 286 those to which the student is actually exposed.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments involved Arabic-speaking students at the American University of Beirut and American universities. Relationship between Edwards' and McClelland's measures of Achievement Motivation with (relatively) culturally unbiased probing of imaginative stories indicated some special traits appearing in Arab language and personality which bear directly and indirectly on Arab behavior vis-b-vis the conflict situations (Melikian, 1958, andBen-Dak, 1969).…”
Section: Facets Of the Confrontationmentioning
confidence: 99%